Lista sistemática de las larvas y juveniles de peces en la Región del Domo de Costa Rica - Aguilar-Ibarra, A; Vicencio Aguilar, M E (Revista de Biología Tropical, 1994)
A checklist of fish larvae and juveniles collected in the epipelagic zone of the Costa Rica Dome (Autumn 1981 and Surnmer 1982 ) ineludes 13 orders, 37 families, 41 genera and 21 species (Osteichthyes)